Investigation of Management of Change (MOC) requirements for framework intervention compliance with Process Safety Management standard - Hanida, Abdul Aziz; Sukadarin, Ezrin Hani; Abdullah, Syamsul B.; Othman, Mohamad R.; Nur Izzati, Pakhor Anuar; Pang, Kar Kei (2019)
Changes and modifications in chemical, oil, and gas plants process are essential for survival in the dynamic process industry. These changes and modifications are needed for a variety of reasons such as yield of improvement, compensation for unavailable equipment, production increases, safety improvements and pollution prevention. However, a number of catastrophic incidents such as Flixborough have been attributed to improperly handled process changes. One of the established standards that addressed the above issue is Process Safety Management (PSM) by OSHA US. The PSM standard contains 14 elements, including Management of Change (MOC) 29 CFR 1910.119(l). MOC has excellent requirements that could and should prevent accidents due the changes if plants follow the regulation as intended. MOC element has been established with interrelated PSM elements such as process safety information, process hazard analysis, operating procedures, training, Emergency Planning and Response and incident investigation that define the management principles to control process hazards and protect the workplace. Less consideration of interrelations between the PSM elements leading to poor data sharing, energy and document intensive which complicates the updating process safety data and knowledge transfer that could contribute to safety and regulation implication. MOC with an integrated risk analysis is an important Process Safety Management (PSM) elements involved in planning and controlling risks and hazards that comes with the proposed change. However, lacking of systematic technique for easy adoption of this element had delayed its application in plant. Corresponding to these weaknesses, an integrated MOC management system is presented in this study. Results of this study comprises of MOC process framework and MOC management system (MOCMS) which acts as a guidance and documentation inventory tool. Other associated frameworks and systems also developed to ease the MOC program. Implementation of this technique and system at the selected plant as a case study shows is examined and discussed. The system is beneficial to industries to manage underlying risks in temporary and emergency change which ease the tracking of MOC case inventory as to improve risk controls in changes.